X-linked lymphoproliferative syndrome. Natural history of the immunodeficiency. - Sullivan, J L (1983)
The X-linked lymphoproliferative syndrome is characterized by immunodeficiency to Epstein-Barr virus (EBV) manifested by severe or fatal infectious mononucleosis and acquired immunodeficiency. We studied immune responses in six males of a well-characterized kindred with the X-linked lymphoproliferative syndrome. Two males were studied before and during acute fatal EBV infection. Both individuals demonstrated normal cellular and humoral immunity before EBV infection. During acute EBV infection, both individuals developed vigorous cytotoxic cellular responses against EBV-infected and -uninfected target cells. Anomalous killer and natural killer T cell activity was demonstrated against a variety of lymphoid cell lines, autologous fibroblasts and autologous hepatocytes. Effector cells responsible for anomalous killing reacted with a pan-T cell monoclonal antibody, and belonged to the OKT.8 T cell subset. Death in each case was caused by liver failure, but one patient developed extensive liver necrosis, whereas the other developed a massive infiltration of the liver with EBV-infected immunoblasts after aggressive immunosuppressive therapy. Immunological studies were performed on four males who had survived EBV infection years previously. They demonstrated global cellular immune defects with deficiencies of lymphocyte proliferative responses to mitogens and antigens, humoral immune deficiencies, abnormalities of regulatory T cell subsets and deficient natural killer cell activity. We propose that an aberrant immune response triggered by acute EBV infection results in unregulated anomalous killer and natural killer cell activity against EBV infected and uninfected cells. These studies suggest that global immune defects appearing in males with X-linked lymphoproliferative syndrome who survive EBV infection are epiphenomenon.